Pengaruh Toxic Leadership, Mental Well-Being terhadap Job Performance yang dimediasi oleh Work Engagement pada Perusahaan Sektor Teknologi Grogol Petamburan - Zulyar, Ratu Vanya Nurin Fathi; Emilisa, Netania; Larasati, Khayla Sekar; Munawar, Mutiah (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze: (1) The influence of Toxic Leadership, Mental Well-Being, Job Performance, Work Engagement in Grogol Petamburan Technology Sector Companies. (2) The Influence of Toxic Leadership on Work Engagement in Grogol Petamburan Technology Sector Companies. (3) The Effect of Toxic Leadership on Job Performance in Grogol Petamburan Technology Sector Companies. (4) Mental Well-Being towards Work Engagement in Grogol Petamburan Technology Sector Companies. (5) Mental Well-Being on Job Performance in Grogol Petamburan Technology Sector Companies. (6) To analyze Work Engagement on Job Performance in Grogol Petamburan Technology Sector Companies. (7) Toxic Leadership on Job Performance is mediated by Work Engagement in the Grogol Petamburan Technology Sector Company. (8) Mental Well-Being on Job Performance is mediated by Work Engagement in the Grogol Petamburan Technology Sector Company. The data analysis method that will be used is adjusted to the research objectives, for the first research objective using SPSS software, for the second, third, fourth, fifth, sixth, seventh and eighth research objectives using Structural Equation Model (SEM) with AMOS software. Based on the research results, it was found that: (1) The results of Toxic Leadership descriptive statistics show that workers feel the existence of Toxic Leadership in Grogol technology sector companies. (2) The results of hypothesis testing show that there is no significant negative influence between Toxic Leadership on Work Engagement. (3) The results of hypothesis testing show that there is no significant negative influence between Toxic Leadership on Job Performance. (4) The results of hypothesis testing show that there is a significant positive influence between Mental Well-Being and Work Engagement. (5) The results of hypothesis testing show that there is a significant positive influence between Mental Well-Being on Job Performance. (6) The results of hypothesis testing show that there is a significant positive influence between Work Engagement and Job Performance. (7) The results of hypothesis testing show that there is no significant influence between Toxic Leadership on Job Performance mediated by Work Engagement. (8) The results of hypothesis testing show that there is a significant influence between Mental Well-Being on Job Performance mediated by Work Engagement.